1999
DOI: 10.1097/00000539-199912000-00038
|View full text |Cite
|
Sign up to set email alerts
|

The Pain Visual Analog Scale: Is It Linear or Nonlinear?

Abstract: A change in the visual analog scale score represents a relative change in the magnitude of pain sensation. Use of the VAS in comparative analgesic trials can now meaningfully quantify differences in potency and efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
104
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(108 citation statements)
references
References 13 publications
0
104
0
2
Order By: Relevance
“…By 1 week post-treatment, there were clinically (≥20/100 mm on the VAS) and statistically significantly differences in the pain scores of the calcitonin group compared with those in the control group. Various studies have investigated the minimum clinically significant change in patients' pain severity measured with a 10-cm VAS and found 1.3 cm as the cutoff [83,84]. This, along with the finding that all studies of acute pain of OVCF reported statistically significant results for the analgesic efficacy of calcitonin, suggests that these results are not due to chance.…”
Section: Discussionmentioning
confidence: 98%
“…By 1 week post-treatment, there were clinically (≥20/100 mm on the VAS) and statistically significantly differences in the pain scores of the calcitonin group compared with those in the control group. Various studies have investigated the minimum clinically significant change in patients' pain severity measured with a 10-cm VAS and found 1.3 cm as the cutoff [83,84]. This, along with the finding that all studies of acute pain of OVCF reported statistically significant results for the analgesic efficacy of calcitonin, suggests that these results are not due to chance.…”
Section: Discussionmentioning
confidence: 98%
“…The scores on the visual analogue pain scale (VAPS; which is a linear function calculation of pain intensity) [21] in the remifentanil-alone group were nearly twice those of the patients in the other groups. Remifentanil alone, therefore, provided notably inferior pain relief compared with epidural analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with knee OA indicated the pain in their afflicted knee using a visual analog scale (VAS) [36]. Body mass index (BMI) was computed for each participant.…”
Section: Methodsmentioning
confidence: 99%